The need and opportunity of establishing a tourism information and promotion center in Oltenia under the mountain / Enea Constanta ...[et al.] - Constanta, Enea; Constantin, Enea; Carina, Stegaroiu; Daniela, Popescu (Universiti Teknologi MARA (UiTM), Malaysia, 2012)
Currently, the access of information regarding data of general interest for Romania, through specialized tourism information and promotion centers (tourist attractions, cultural and business events, archaeological sites, accommodation structures, restaurants, facilities for leisure or any other facilities accompanying a tourist journey or of tourist interest or leisure facilities in short), is almost impossible due to the lack or sporadic existence of such centers. Tourist areas do not have a suitable network of multi-function centers specialized in tourism, allowing tourists access to information and information services as well as special events. In fact, the level of promotion and development of tourist information centers is now extremely reduced therefore, creating a national network of tourism information and promotion centers (NCTIP) is extremely important for promoting the Romanian tourism.